Penerapan Metode Pembelajaran Diskusi Terhadap Kemampuan Berbicara Siswa Pada Mata Pelajaran Bahasa Indonesia Dikelas V SDN Kiyonten 1 - Musta’in, Annisatul Lutfiana; Koesmadi, Dita Primashanti; Afifah, Uci Ulfa Nur (LP. Ma'arif Janggan Magetan, 2024)
This study was conducted with the aim of identifying how far the group discussion learning method can improve the speaking skills of grade V students of SDN Kiyonten 1. The type of research carried out is qualitative descriptive. The technique used to analyze the data is from the mils and huberman technique. The findings or results of research that have been conducted regarding the application of discussion learning methods to students' speaking skills have the results that, discussion learning methods can increase the level of student participation in learning that makes students dare to express their opinions. The application of discussion learning methods can improve speaking skills in students. In addition, the discussion method also provides benefits in improving students' speaking skills and making learning more interesting and interactive. It can be concluded that the implementation of the discussion learning method on students' speaking skills in Indonesian subjects in grade V SDN Kiyonten 1 has often been applied and is effective to use.